Collagen-coated polylactic-glycolic acid (PLGA) seeded with neural-differentiated human mesenchymal stem cells as a potential nerve conduit. - Sulong, Ahmad Fadzli; Hassan, Nur Hidayah; Ng, Min Hwei; Lokanathan, Yogeswaran; Naicker, Amaramalar Selvi; Abdullah, Shalimar; Yusof, Mohd Reusmaazran; Htwe, Ohnmar; Idrus, Ruszymah; Mohamed Haflah, Nor Hazla (Wroclaw Medical University, 2014)
Background. Autologous nerve grafts to bridge nerve gaps pose various drawbacks. Nerve tissue engineering to promote nerve regeneration using artificial neural conduits has emerged as a promising alternative. Objectives. To develop an artificial nerve conduit using collagen-coated polylactic-glycolic acid (PLGA) and to analyse the survivability and propagating ability of the neuro-differentiated human mesenchymal stem cells in this conduit. Material and Methods. The PLGA conduit was constructed by dip-molding method and coated with collagen by immersing the conduit in collagen bath. The ultra structure of the conduits were examined before they were seeded with neural-differentiated human mesenchymal stem cells (nMSC) and implanted sub-muscularly on nude mice thighs. The non-collagen-coated PLGA conduit seeded with nMSC and non-seeded non-collagen-coated PLGA conduit were also implanted for comparison purposes. The survivability and propagation ability of nMSC was studied by histological and immunohistochemical analysis. Results. The collagen-coated conduits had a smooth inner wall and a highly porous outer wall. Conduits coated with collagen and seeded with nMSCs produced the most number of cells after 3 weeks. The best conduit based on the number of cells contained within it after 3 weeks was the collagen-coated PLGA conduit seeded with neuro-transdifferentiated cells. The collagen-coated PLGA conduit found to be suitable for attachment, survival and proliferation of the nMSC. Minimal cell infiltration was found in the implanted conduits where nearly all of the cells found in the cell seeded conduits are non-mouse origin and have neural cell markers, which exhibit the biocompatibility of the conduits. Conclusions. The collagen-coated PLGA conduit is biocompatible, non-cytotoxic and suitable for use as artificial nerve conduits